Developing Programming Competence Among Physics Education Students With Multi-Platform E-Learning During COVID-19 - Syahid, Muhammad Taufik; Sutrio, Sutrio; Wahyudi, Wahyudi; Zuhdi, Muhammad; Arduha, Jannatin (Prodi Fisika FKIP Unram, 2023)
This research examines the effectiveness of a multi-platform e-learning approach in developing programming competence among physics education students at Mataram University's Faculty of Teaching and Education during the COVID-19 pandemic. The R2D2 model, an iterative and cyclical constructivist learning design process emphasizing creative learning experiences, serves as the methodological framework. Data collection employs questionnaires and tests. The research yields two primary findings: the development of a multi-platform e-learning media for a computer programming course by combining features from SIA, SPADA Unram, YouTube Channel, Google Drive, and WhatsApp groups; and student learning outcomes falling within the